Etika Perang Dalam Islam - Adib, Shohil (Tasamuh: Jurnal Studi Islam, 2017)
This paper aims to determine how far and a great morale shown by the Prophet Muhammad in a war situation and to lead a country. By using this method, cross-check is the main aspect in the historical method, of course, after reviewing the literature (libraryresearch) beforehand. So that the data that has been collected in the literature, the author then process them to pass through three stages, namely the description, interpretation, and critical analysis in order to maintain the validity and factuality of what is generated from this study in an academic perspective. it mentioned through a variety of processes, the authors try to conclude in order to answer fundamental problem that consists of how the ethics of war committed by the Prophet Muhammad? Aspects of what is being charge of the ethical principles? From the second formulation of the problem, the author is able to present an outline of the conclusions as follows, in general that ethics of war played by the Prophet Muhammad is a war that is based on the three grounds were very urgent in human rights, first, the war carried out for defending Muslim beliefs and morals of the people, second, to defend dignity, country property and other proprietary, third, to give a lesson to traitors and opponents of Islam. There are the three reasons why we are allowed to fight. After the war carried out there a code of conduct that should be adhered to, for the example we forbidden to kill women and children, and the priests were not allowed to fight against those who are not involved in wars, do not burn people’s homes, and trees